2024
DOI: 10.1109/tvcg.2023.3241581
|View full text |Cite
|
Sign up to set email alerts
|

uxSense: Supporting User Experience Analysis with Visualization and Computer Vision

Abstract: Analyzing user behavior from usability evaluation can be a challenging and time-consuming task, especially as the number of participants and the scale and complexity of the evaluation grows. We propose UXSENSE, a visual analytics system using machine learning methods to extract user behavior from audio and video recordings as parallel time-stamped data streams. Our implementation draws on pattern recognition, computer vision, natural language processing, and machine learning to extract user sentiment, actions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Additionally, expert feedback suggested that the SI model for narrative maps held potential value for analysts in their sense-making processes. Batch et al [19] introduced uxSENSE, a visual analytics system leveraging machine learning techniques to extract user behavior from audio and video recordings. The proposed method extracts multi-modal features of human behavior, including user sentiment, actions, posture, spoken words, and other relevant features, from such recordings.…”
Section: Capturing and Analyzing Semantic User Interactions In Visual...mentioning
confidence: 99%
“…Additionally, expert feedback suggested that the SI model for narrative maps held potential value for analysts in their sense-making processes. Batch et al [19] introduced uxSENSE, a visual analytics system leveraging machine learning techniques to extract user behavior from audio and video recordings. The proposed method extracts multi-modal features of human behavior, including user sentiment, actions, posture, spoken words, and other relevant features, from such recordings.…”
Section: Capturing and Analyzing Semantic User Interactions In Visual...mentioning
confidence: 99%
“…Additionally, expert feedback suggested that the SI model for narrative maps holds potential value for analysts in their sensemaking processes. Batch et al [18] introduced uxSENSE, a visual analytics system leveraging machine learning techniques to extract user behavior from audio and video recordings. The proposed method extracts multi-modal features of human behavior, including user sentiment, actions, posture, spoken words, and other relevant features, from such recordings.…”
Section: Capturing and Analyzing Semantic User Interactions In Visual...mentioning
confidence: 99%
“…Computer vision techniques involve analyzing and understanding digital images and videos with the help of algorithms and mathematical models. (Batch et al, 2023) propose UXSense -a method for extracting multi-modal features of human behavior from video and audio footage using machine learning (ML) to support UX and usability professionals in their analysis of user session data using interactive visualization. Furthermore, computer vision in video analysis has gained tremendous attention in recent years.…”
Section: Ux and Machine Learning -Preprocessing Of Audiovisual Data U...mentioning
confidence: 99%